Survey on Preserving Data Privacy in Cloud - Paul, Bincy; Azath, M (International Journal of Computer Sciences and Engineering, 2014)
Cloud computing is the future of information technology. It demonstrates all the big trends in the design and use of computer architectures. With cloud computing, it is necessary for data to be not only stored in the cloud but also shared across multiple users, when the data are sharing privacy breach of the data can occur. In cloud computing preserving data privacy is an important task because the data itself contains sensitive information. A basic solution for preserving data privacy is to encrypt the data, and then upload the encrypted data into the cloud. As next give a data access notification to the data owner, providing complete permission of control to the user over the data. Designing an efficient and secure data sharing scheme for groups in the cloud is not an easy task. Oruta is the first privacy-preserving mechanism for shared data stored in the cloud. By using homomorphic authenticable ring structures, it gives privacy preserving public auditing for secure clouds to storage system. This survey analyzes various techniques for preserving shared data privacy in the cloud.